Investigating HOTS on Reading Questions from Fiction Text of the English Textbook Used by Vocational High Schools in Indonesia - Dhina Shinto Wresni; Mauly Hikmat Halwat; Muamaroh Muamaroh (AL-ISHLAH: Jurnal Pendidikan, 2023)
Higher-order thinking skills become the target for learning outcomes in the current curriculum. The integration of those thinking levels must be included in the textbook. The English textbook is a kind of media for the students and teachers doing the learning process. A qualified book should provide HOTS instructions to achieve the current curriculum’s goal. This study aims to analyze the use of HOTS in reading questions in fiction texts and find the most dominant thinking skills used. This study was descriptive qualitative research. The data was the reading questions on fiction texts, and the data source is an English textbook titled “English In Mind” a  second edition published by the Ministry of Research, Technology and Higher Education Indonesia for grade X used by Vocational High Schools.  The researcher used documentation as the collecting data technique, and the technique of analyzing data used was from Miles and Huberman. They are data collection, reduction, and display; the last is the conclusion or verification. The finding of this study is this book has developed HOTS. 53,33% belong to C4, and 46,66% belong to C5 level and the most dominant thinking skillare at C4 or analysis level. The conclusion is that eight fiction texts contain fifteen reading questions integrating HOTS.